Dabigatran-associated drug exanthema and its increasing prevalence - Jaiswal, Shashank; Jaiswal, Aditi; Kaul, Subhash (Indian Journal of Case Reports, 2026)
Anticoagulants are commonly associated with hemorrhagic complications. However, rare hypersensitivity drugreactions associated with direct oral anticoagulants (DOACs) in the form of cutaneous reactions such as vasculitis,exanthema, and urticaria are also being reported. With the increase in the use of DOACs over warfarin as the choiceof anticoagulant in the treatment of atrial fibrillation, as well as venous thromboembolism, recently, there has been a rise in the number of reported cutaneous adverse effects. This case report describes the clinical course of a 29-year-old postpartum patient being treated for cerebral venous sinus thrombosis, who experienced Dabigatran-induced exanthema. We further provide a review of all the cases reported so far.